Analisis Pemanfaatan Artificial Intelligence dalam Pengembangan Teknologi Pembelajaran Pendidikan Agama Islam di Madrasah - Nurul Aini; Sita Acetylena (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed various sectors, including education. In Islamic Religious Education (IRE), AI offers opportunities to enhance learning technologies through adaptive learning resources, personalized instruction, lesson planning, and digital learning media development. However, AI implementation also raises challenges related to the accuracy of religious information, academic ethics, data privacy, and the evolving role of teachers. This study aims to analyze the development of AI utilization in Islamic Religious Education, identify its opportunities in educational technology development, and examine the ethical challenges associated with its implementation in madrasahs. This study employed a qualitative descriptive approach using library research. Data were collected through documentation studies of scholarly articles, books, and relevant policy documents and analyzed using content analysis techniques. The findings indicate that AI can improve learning effectiveness by supporting instructional material development, interactive learning media, assessment design, and personalized learning experiences. Nevertheless, its implementation requires teachers' digital literacy, careful verification of AI-generated information, and adherence to Islamic ethical values to ensure that AI serves as a supportive educational tool rather than replacing the essential role of teachers. Therefore, integrating AI into Islamic Religious Education should prioritize pedagogical, ethical, and spiritual considerations. Keywords: Artificial Intelligence, Educational Technology, Islamic Religious Education, Madrasah, Library Research